Identifikasi Klasifikasi Jenis Tanah Berdasarkan Nilai Kecepatan Gelombang Geser Vs30 di Daerah Bekasi - Rahman, Aditya Setyo; Sutiyono, Sutiyono; Cindiwati, Cindiwati; Alfiandy, Solih (Buletin GAW Bariri (BGB), 2024)
The complex geological and tectonic conditions of Bekasi are interesting to study the soil layers for sustainable development. This research was conducted to analyze soil types in the Bekasi area based on the USGS topographic Vs30 value. The data used were 613 research location points with a distance of approximately 1 km. The results showed that the Vs30 value in the Bekasi area ranged from 125.5479965 m/s to 316.0310059 m/s. Based on SNI 1726:2019, the entire Bekasi area is classified as soft to medium soil types. The majority of all sub-districts in Bekasi have a soft soil type classification, such as in the areas of Muaragembong, Cabangbungin, Babelan, Tarumajaya, Tambelang, Sukatani, Pebayuran, Kedung Waringin, and parts of Tambun. The medium soil type classification is in the southern part of Tambun sub-district, a small part in the southern part of Tambelang and Sukatani sub-districts, and a small part in the north and south of Muaragembong sub – district.